Development and Disorders of the Airway in Bronchopulmonary Dysplasia - Douglas Bush; Courtney Juliano; Selina Bowler; Caterina Tiozzo (Children, 2023)
Bronchopulmonary dysplasia (BPD), a disorder characterized by arrested lung development, is a frequent cause of morbidity and mortality in premature infants. Parenchymal lung changes in BPD are relatively well-characterized and highly studied; however, there has been less emphasis placed on the role that airways disease plays in the pathophysiology of BPD. In preterm infants born between 22 and 32 weeks gestation, the conducting airways are fully formed but still immature and therefore susceptible to injury and further disruption of development. The arrest of maturation results in more compliant airways that are more susceptible to deformation and damage. Consequently, neonates with BPD are prone to developing airway pathology, particularly for patients who require intubation and positive-pressure ventilation. Airway pathology, which can be divided into large and small airways disease, results in increased respiratory morbidity in neonates with chronic lung disease of prematurity.